2010
DOI: 10.1007/s13187-010-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrics/Gynecology Residents’ Knowledge of Hereditary Breast and Ovarian Cancer and Lynch Syndrome

Abstract: Although there have been many studies regarding physicians' knowledge of hereditary cancer syndromes, very little information exists regarding medical residents' knowledge of hereditary cancer syndromes. Obstetrics/gynecology residents completed a test which evaluated their knowledge of hereditary breast and ovarian cancer and Lynch syndrome. Areas of relative deficit were identified. Residents indicated a desire and need for more education regarding this topic. Cancer genetics education programs should place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Nevertheless, most of these were conducted among specialists, while only one referred to residents [18]. Younger age [20] and recent graduation from medical school [21], as well as being in medical practice less than 10 years [11], have been previously reported as predictors of better knowledge on genetic tests and increased confidence in using them in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most of these were conducted among specialists, while only one referred to residents [18]. Younger age [20] and recent graduation from medical school [21], as well as being in medical practice less than 10 years [11], have been previously reported as predictors of better knowledge on genetic tests and increased confidence in using them in everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…34,35,38,39,41,42,44,[47][48][49][50]55,58 In seven studies, objective knowledge was assessed with a survey utilizing a scale or test to measure accurate understanding of basic genetic principles, clinical practice guidelines, and/or features of hereditary cancer syndromes. 35,38,39,42,47,48,50 In the other six studies, case scenarios or standardized patients were used to measure PCPs' abilities to identify high-risk patients and appropriate genetic testing situations. 32,34,41,44,49,55 Aside from articles reporting on the same sample, 38,48 there was no overlap in measures.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
“…53 Ten studies examined PCPs' self-reported subjective or perceived knowledge. 33,37,[42][43][44][45]47,50,51,55 Although there was no overlap in measures, studies consistently reported a lack of PCPs' confidence in their genetic testing-related knowledge. For example, in a cross-sectional survey of 1311 family practitioners, 54% were not confident in their knowledge of genetic testing in primary care including testing for breast cancer risk.…”
Section: Knowledge Of Genetic Tests For Cancer Riskmentioning
confidence: 99%
“…Adding to existing literature, results from this study reinforce the need for CME training to help launch a better hereditary CRC knowledge base across PCPs [27,32,33,34,35,36,37]. Though patients with a past or present diagnosis of cancer are often under the care of specialists, studies show that communication between specialists and PCPs improve adherence to recommended testing, surveillance and care for other comorbid conditions [38,39].…”
Section: Discussionmentioning
confidence: 56%
“…In a 2010 study examining 65 obstetrics/gynecology residents' practices and knowledge of HBOC and Lynch syndromes, half of the participants incorrectly identified CRC as associated with HBOC; 26 and 41% of participants were unable to respectively identify endometrial and ovarian cancers as cancers associated with Lynch syndrome. Most notably, 76% of participants expressed a desire and need for more education in hereditary cancer and genetic testing [34]. …”
Section: Discussionmentioning
confidence: 99%